EFEKTIVITAS PENERAPAN SCIENTIFIC CRIME INVESTIGATION TERHADAP PEMBUKTIAN DALAM PERKARA PIDANA - ADITYA WARMAN; M. SYUKRI AKUB; WIWIE HERYANI (jurnal.unprimdn.ac.id, 2021)
This study aims to analyze the effectiveness of the application of Scientific Crime Investigation in proving criminal cases and the urgency of implementing scientific crime investigation in proving criminal cases This research was conducted using empirical research methods. The data obtained, both primary and secondary data, are categorized according to the type of data. Then the data was analyzed using qualitative methods The results of this study indicate that: 1). The application of Scientific Crime Investigation (SCI) in proving a crime is a quality assurance and quality control, where in proving a crime, the application plays an important role in minimizing errors that often occur when processing evidence, and without any certain facilities and facilities, it is impossible for law enforcement to take place smoothly. Such facilities or facilities include, among others, educated and skilled human workers, good organization, adequate equipment, sufficient finances and so on. 2) Science in proving criminal cases has a broad understanding that covers almost all disciplines used to conduct investigations. The application of science through the scientific crime investigation (SCI) method is a breakthrough in the evidentiary process in proving a crime. Proof of criminal cases by SCI cannot be separated from the assistance of the Forensic Laboratory, which is the place for checking evidence using scientific knowledge